The effect of treatment protocol on calcaneus bone mineral densitometry after intra-articular calcaneal fractures - Catma, Faruk Mehmet; Unlu, Serhan; Sevgili, Ubeydullah; Ozturk, Alper; Yuksel, Sinan; Altay, Murat (The European Research Journal, 2016)
Objective. To identify the effect of treatment protocol on calcaneus bone mineral density of calceneal fractures treated with different methods. Methods. Sixty-three patients with intra-articular calcaneal fractures were observed prospectively. Patients were classified according to their treatment protocols such as; conservative treatment with short leg plaster cast (Group C), closed reduction and fixation with cannulated screws (Group S) and open reduction internal fixation with plate and screws (Group P). All patients’ bilateral radiographies, CT scans, the American Orthopaedic Foot and Ankle Society (AOFAS) scores and calcaneus bone mineral density measurements by G&E Archilles Quantitative Ultrasound method were obtained at 15th month of follow up period. Results. Fourteen (22%) patients were female and 49 (88%) were male. The mean age was 43.7±12.1 years. The mean follow-up was 33.7±14.7 months. Bone mineral density measurements were calculated as; t scores; -1.48±1.24 for group C, -1.48±1.31 for group S, -0.27±1.68 for group P and z scores; -0.18±1.41 for group C, -0.17±1.9 for group S, 0.96 ± 1.54 for group P. Group P had the higher t and z scores of injured sides than other groups (p=0.008 and p=0.026, respectively). Average AOFAS scores were 78.13±13.04 in group S, 82.58±10.81 in group P and 79.82±11.75 in group C. No significant differences were detected between groups regarding AOFAS scores. Conclusion. Measurement of calcaneus bone mineral density which we used in our study is a method for evaluation of calcaneal fracture treatments and higher density values were found in open reduction and internal fixation group. This may be owing to better control of defect with the allograft and early mobilization by the evident improvement in angular correction.